PACITAN DISTRICT GOVERNMENT POLICY IMPLEMENTATION IN THE SUGAR COCONUT INDUSTRY PROMOTION AND DEVELOPMENT ON FTA - *, Supomo; Sukoharsono, Eko Ganis; Bangun, Wike; Setyowati, Endah (Accounting Department,, 2019)
The implementation of free trade agreements has consequences for product competitiveness, both competitiveness in the international market and competitiveness in the domestic market (Ministry of Trade of the Republic of Indonesia, 2011). An alternative strategy that can be done in an effort to deal with free trade is to create and produce superior products that are not the result of assistance from other countries, so that these goods have a strong bargaining position in the global economy. One industry that is local and has the advantage of this product is the coconut sugar industry. One of the best coconut sugar producers in Indonesia is Pacitan Regency. The importance of the industry based on coconut sugar for the people in Pacitan Regency has an important value, so that the function and role of the government is very much needed to increase the existing coconut sugar industry. The purpose of this study was to analyze the potential of coconut sugar SMEs in Pacitan District, analyze the constraints in the development of coconut sugar SMIs and analyze the role of local governments in facilitating coconut sugar SMEs. Retrieval of data in this study includes field observations, document studies and interviews with all stakeholders such as coconut sugar industry players, consumers, Micro Cooperative and Business Services and the Pacitan Regency Industry and Trade Office. Data analysis techniques use interactive analysis. Pacitan Regency is one of the best coconut sugar producing regions in Indonesia with a total of brown sugar industry which is as many as 5,115 units. This sugar industry can absorb 10,220 workers or 39.03% of the workforce in Pacitan Regency. This is due to the large number of raw materials in the area of Pacitan Regency. The coconut sugar industry is currently experiencing two obstacles in its production process and marketing. The Micro Cooperative and Business Office and the Pacitan Regency Industry and Trade Office in order to increase coconut sugar SMIs carry out coaching and facilitation. The guidance and facilitation includes training, work equipment facilities, product legality facilities, promotional facilities and capital facilities.